2018
DOI: 10.26822/iejee.2018541310
|View full text |Cite
|
Sign up to set email alerts
|

School Violence: School Administrators Perspectives and Ways of Solution in TURKEY

Abstract: The purpose of this study is to determine the ways primary education administrators solve events of violence as a problem. To this end, sample cases of violence were derived from the school violence news appearing on media organs in the last four years. They were categorized based on the type of violence. Data were collected via a semi-structured interview form developed by the researcher and administered to school administrators. In-depth data were collected in regard to the ways they would solve problems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Firstly, the participants conducted the study within a framework of legal legislation in order to create content related to their own specific subject areas. Despite the existence of legislation, there have been notable information and perception deficiencies in its implementation (Çalık et al, 2018;Hernandez et al, 2010). For this reason, integrating appropriate content into the materials design and construction was an important area of critique, which was successfully achieved by the preservice teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the participants conducted the study within a framework of legal legislation in order to create content related to their own specific subject areas. Despite the existence of legislation, there have been notable information and perception deficiencies in its implementation (Çalık et al, 2018;Hernandez et al, 2010). For this reason, integrating appropriate content into the materials design and construction was an important area of critique, which was successfully achieved by the preservice teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The school community should support and be involved in preventing all forms of violence and bad behaviour at school. The youth and adults in the school community must act as really authority figures and role models (Çalık, Tabak, & Tabak, 2018)). They should be incorporated in the running of crime prevention programmes so that the complimentary role of school and community is made manifest in the life of schools.…”
Section: Introductionmentioning
confidence: 99%
“…The emotional identity of a class or a school is a distinctive feature from others. It is reported that teachers who experience negative emotions and reflect them in their actions negatively affect the development of students and schools in various aspects (Çalık, Tabak and Yavuz Tabak, 2018;Demirtaş and Küçük, 2016;Gasser, Grütter, Buholzer and Wettstein, 2018;Schenke, Ruzek, Lam, Karabenick and Eccles, 2018). The contradictory demands of complex work-life relationships can drag individuals into fear and anxiety (Morgan, 2010).…”
Section: Introductionmentioning
confidence: 99%